An Increase in Male Recombination Rate With Age in Dairy Cattle Is Heritable and Polygenic - Jade E; Littlejohn MD; Eketone K; Spelman RJ; Stapley J; Santure AW (John Wiley and Sons Ltd, 2025)
Meiotic recombination is an essential process for shuffling genetic diversity in sexually reproducing organisms, can vary within and between individuals in response to intrinsic and extrinsic factors, and can be heritable. Interestingly, recombination rate has been found to vary with age in some species, but to date, there have been no assessments of the heritability and genetic architecture of this age effect. Here, we leverage a large pedigree of SNP chip-genotyped Aotearoa New Zealand Holstein-Friesian and Jersey dairy cattle to test for an effect of age on male recombination rate, the heritability of recombination rate and of any such age effect on recombination, and the genetic architecture underlying these two phenotypes. We found a significant, albeit small, increase in the average number of male autosomal recombinations with age. Consistent with previous studies, we found moderate heritability (h2 ≈ 0.15) of sire recombination rate and detected association with several regions on chromosome 10 encompassing genes such as REC8, REC114, RNF212B and NEK9. Further, we found novel evidence of some heritability (h2 ≈ 0.05) in the rate of change in recombination with age in sires. Variation in the rate of change with age is likely also polygenic, but there is a region on chromosome 1 that is weakly associated with the rate of change. It is unclear whether the heritability of age-related recombination rate change is widespread across species, and we encourage studies in other taxa to assess its prevalence and evolutionary significance.
Keywords: age-related change; Bos taurus; crossing over; meiosis; recombination rate